Facilitating islet transplantation using a three-step approach with mesenchymal stem cells, encapsulation, and pulsed focused ultrasound - Razavi, Mehdi (Stem Cell Res Ther, 2020)
BACKGROUND: The aim of this study was to examine the effect of a three-step approach that utilizes the application of adipose tissue-derived mesenchymal stem cells (AD-MSCs), encapsulation, and pulsed focused ultrasound (pFUS) to help the engraftment and function of transplanted islets. METHODS: In step 1, islets were co-cultured with AD-MSCs to form a coating of AD-MSCs on islets: here, AD-MSCs had a cytoprotective effect on islets; in step 2, islets coated with AD-MSCs were conformally encapsulated in a thin layer of alginate using a co-axial air-flow method: here, the capsule enabled AD-MSCs to be in close proximity to islets; in step 3, encapsulated islets coated with AD-MSCs were treated with pFUS: here, pFUS enhanced the secretion of insulin from islets as well as stimulated the cytoprotective effect of AD-MSCs. RESULTS: Our approach was shown to prevent islet death and preserve islet functionality in vitro. When 175 syngeneic encapsulated islets coated with AD-MSCs were transplanted beneath the kidney capsule of diabetic mice, and then followed every 3 days with pFUS treatment until day 12 post-transplantation, we saw a significant improvement in islet function with diabetic animals re-establishing glycemic control over the course of our study (i.e., 30 days). In addition, our approach was able to enhance islet engraftment by facilitating their revascularization and reducing inflammation. CONCLUSIONS: This study demonstrates that our clinically translatable three-step approach is able to improve the function and viability of transplanted islets. [Image: see text]